2021
DOI: 10.1155/2021/3725316
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Directs T Helper Cells toward Th1 Cell Differentiation via the STAT1‐T‐Bet Pathway

Abstract: Dexmedetomidine is an α2 adrenergic receptor agonist that has been reported to modulate the polarization of CD4+ T cells. However, the underlying mechanisms by which dexmedetomidine induces T-helper 1 (Th1) cell differentiation remain poorly understood. The aim of this study was to explore the potential mechanisms through which dexmedetomidine can induce Th1 cell differentiation. Purified CD4+ T cells were stimulated with anti-CD3/anti-CD28 and then treated with dexmedetomidine. Flow cytometry analysis was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Studies have shown that STAT1 can cause CD4+ T cells to differentiate into Th1, and its signaling pathway blocks GATA-3 transcription, thus suppressing Th2 differentiation and controlling Th1/Th2 balance. 36 , 37 IL-27, a member of the IL-12 family, has a significant part in the immune response and can directly trigger apoptosis in tumor cells by engaging with various immune cells in the body, such as CD4+ T cells, CD8+ T cells, regulatory T cells, natural killer cells, and dendritic cells. Moreover, IL-27 stimulates immune cells to release particular cytokines, thus controlling both cellular and humoral immunity and indirectly restraining tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that STAT1 can cause CD4+ T cells to differentiate into Th1, and its signaling pathway blocks GATA-3 transcription, thus suppressing Th2 differentiation and controlling Th1/Th2 balance. 36 , 37 IL-27, a member of the IL-12 family, has a significant part in the immune response and can directly trigger apoptosis in tumor cells by engaging with various immune cells in the body, such as CD4+ T cells, CD8+ T cells, regulatory T cells, natural killer cells, and dendritic cells. Moreover, IL-27 stimulates immune cells to release particular cytokines, thus controlling both cellular and humoral immunity and indirectly restraining tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…These phosphorylation events play a critical role in dictating T cell fates and functions. The phosphorylation of specific transcription factors, such as signal transducer and activator of transcription 1 (STAT1) in Th1 cells, STAT6 in Th2 cells, and STAT3 in Th17 cells, contributes to their differentiation and functional specialization (17)(18)(19)(20)(21). In patients with HCC, Th1 cytokines of serum level are often suppressed, while Th2 cytokines are frequently elevated (22).…”
Section: Phosphorylationmentioning
confidence: 99%